LANGUAGE USE FOR CRITICIZING TROUGH STAND UP COMEDY SHOW: PRAGMATIC APPROACH - Ika Susanti (Pusat Riset dan Inovasi Nasional, 2022)
The use of language can be classified into some points. One of them is for criticizing. This paper focused in analyzing the use of language in criticizing. The data was taken from stand up comedy shows. Qualitative is used in elaborating the data of the research. There are 5 stand up comedy videos that was used as data. This papers used three dimensions of theories, those are context, presupposition and implicature, in order to know how the comic deliver a critique in their stand up comedy. As the result, the use of pragmatic can be showed how language can be applied in giving a critique. The information of context and presupposition support in understanding the implicature of the comics’ utterance. Briefly, I can conclude that Comic in this paper gave critiques to the government attitude, government policy and enforcer attitude.